Media Transformation Model by Digitization: Case Study of Cartography Material At Badan Arsip dan Perpustakaan Provinsi Jawa Tengah - Narendra, Albertus Pramukti (Record and Library Journal, 2016)
The rapid growth of information is supported by the development of information and communication technologies, especially digital information. On the other hand, the information that hasnât been digitalized but has long-term benefit values in order to persist through the media transfer processes. The library and archive institution playing the role to manage the various documents so that people can access them needs to preserve the documents in order to give benefits for the future generation. The library and archive institution of Central Java as the institution managing the information has preserved various documents such as cartography documents. This case study research focused on the transformation model of cartography documents in which its contents should be preserved through scanning processes. The results showed that the processes, facilities, technical specification, application tool of the media transformation activities, and storage process of the preserved documents were to preserve the information values within.Â  Â Â